Determination of Some Plant Characteristics, Nutritive Value and Seed Germination Rates of Ranunculus constantinopolitanus - Erdal Çaçan; İhsan Arslan (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out to determine the plant characteristics, nutritive value and seed germination rate of the Ranunculus constantinopolitanus plant, which is found intensely in meadow-pasture areas and can have toxic effects on animals when consumed. The plant material of this study consists of 50 Ranunculus constantinopolitanus plants collected by random sampling method from the meadow area in Çayağzı village located in Bingöl city center in 2018. Plant length of Ranunculus constantinopolitanus 39-70 cm, stem diameter 1.83-5.53 mm, number of flowers in the plant 3-17, number of leaves in the plant 4-10, leaf length 3-7 cm, leaf width 4-8 cm, plant dry weight 0.75-3.33 grams, stalk ratio in plant 35.1-86.5%, leaf ratio in plant 3.9-42.7%, flower ratio in plant 4.0-43.4%, number of fruit in plant 4.0-11.0, number of achene in fruit 18.0-36.0, number of achene per plant 26-180 and thousand seed weight of achene varied between 4.31-5.03 grams. The dry matter ratio of Ranunculus constantinopolitanus 90.5-90.6%, crude protein ratio 13.1-13.4%, ADF ratio 34.9-35.9%, NDF ratio 47.3-48.9%, ADP ratio 0.33-0.37%, Ca ratio 1.16-1.22%, Mg ratio 0.37-0.38%, P ratio 0.26-0.27% and K ratio varied between 0.94-0.97%. As a result of the germination test with plant seeds, it was determined that 87 seeds germinate at the end of the 21st day, and the total germination rate was 21.8%. Detection of toxic substances and other nutrients contained in this plant with future studies will provide better recognition of this plant.